The Implementation of Improved Advanced Encryption Standard and Least Significant Bit for Securing Messages in Images - Pujiono, Imam Prayogo; Rachmawanto, Eko Hari; Nugroho, Dicky Anggriawan (Universitas Dian Nuswantoro and IndoCEISS, 2023)
Security and confidentiality are essential aspects needed in the process of exchanging messages. Maintaining the message's security and confidentiality can be done by encrypting the message with cryptographic techniques to protect the message. However, the encrypted message (ciphertext) usually raises suspicion from eavesdroppers so that they try to unravel the contents of the message or damage the contents of the message or prevent the message from reaching the intended recipient. To avoid eavesdroppers' suspicion of encrypted messages, after encryption, the ciphertext can then be inserted into an image using steganography techniques so that eavesdroppers do not know whether there is a secret message in an image. In this research, the authors use the Improved AES-128 (Advanced Encryption Standard) Algorithm to encrypt messages and LSB (Least Significant Bit) Algorithm to insert ciphertext into an image. Where the AES Algorithm Improvement is made by adding a sending and receiving applications ID to modify the Key Schedule process, with modifications to the Key Schedule process, messages can only be read on the original recipient's cellphone by entering the correct key. The results of this study show that eavesdroppers do not easily know the existence of the ciphertext, besides that even if the eavesdroppers get the ciphertext and know the encryption key, the message remains unreadable on their cellphone because the ID of the application sending or receiving the message has changed.